The Influence Of Social Media on Msme Product Marketing: A Meta-Analysis (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aims to determine the influence of social media on the marketing of micro, small, and medium enterprises (MSMEs). The study employs a meta-analysis method by reviewing several articles from national journals accessible online through Google Scholar. The meta-analysis uses a sample of 15 relevant articles from national journals focusing on the impact of social media on MSME product marketing from 2020 to 2024. Based on data from the 15 journals, the findings reveal that social media significantly positively impacts MSME product marketing. It demonstrates that social media plays a crucial role in increasing product awareness and reaching a broader audience. Social media enables MSMEs to promote their products more creatively, visually, and interactively, resulting in more effective sales growth.